THE DIGITAL REVOLUTION AND IMPLICATIONS OF INDUSTRY 4.0 - Mjwara, Kimberley (The IIE, 2019)
The 4th Industrial Revolution is ultimately an era of cyber-physical systems powered by the breakthroughs in nanotechnology providing a performance boost a adding a new functionality to the internet of things, biotechnology, virtual reality, robotics, artificial intelligence. Industry 4.0 is significant as it will change and affect how organizations operate and communicate to its stakeholders. The purpose of this study is to investigate the impact of technology and digitization on brand business models and ultimately the overall marketing industry. Specific focus has been given to the web 4.0 paradigm. This research will also assess how brands now communicate to their consumers using digital innovations as well consumer responses. Ultimately this study aims to evaluate the effectiveness and compatibility of brands, social media, and technology in today’s Fourth Industrial Revolution.
Keywords: Brand; Brand communication; Social media; Digital communication; Artificial Intelligence